2010
DOI: 10.1016/j.juro.2009.09.076
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Glycol Induced Hyperoxaluria Increases Plasma and Renal Tissue Asymmetrical Dimethylarginine in Rats: A New Pathogenetic Link in Hyperoxaluria Induced Disorders

Abstract: Increased systemic and local tissue asymmetrical dimethylarginine may help explain the pathogenetic mechanisms of hyperoxaluria induced disorders such as nephrolithiasis and atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Some recent studies reported a local relationship of endothelial nitric oxide synthase in experimentally induced hyperoxaluric animals [10]. But, in one of our recent studies, we demonstrated that hyperoxaluria induces both local and systemic endothelial dysfunction as shown by increased plasma Asymmetrical Di Methyl Arginine (ADMA) levels which is a measure of endothelial dysfunction [11].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Some recent studies reported a local relationship of endothelial nitric oxide synthase in experimentally induced hyperoxaluric animals [10]. But, in one of our recent studies, we demonstrated that hyperoxaluria induces both local and systemic endothelial dysfunction as shown by increased plasma Asymmetrical Di Methyl Arginine (ADMA) levels which is a measure of endothelial dysfunction [11].…”
Section: Introductionmentioning
confidence: 75%
“…Since urolithiasis is a systemic metabolic disorder, the idea of dysfunction in endothelium merits consideration. First study on this relationship was carried out by Aydin et al [11] they have shown that asymmetrical dimethyl arginine increased early in the hyperoxaluric mileu both in local renal tissue and systemic circulation. Linas and Repine had shown that renal proximal epithelial cell transport was controlled by nearby endothelial tissue [9].…”
Section: Discussionmentioning
confidence: 99%
“…A possible role of vascular endothelium on stone formation through NOS on epithelium ion transport has been suggested previously [ 15 ]. Aydin [ 5 ] firstly showed the effect of endothelium on calcium oxalate (CaOx) stone formation and outlined an increased local and systemic ADMA in an ethylene glycol-induced hyperoxaluria rat model. ADMA, as an endogenous competitive inhibitor of NOS, has been linked to ED, atherosclerosis, and mortality in patients with peripheral arterial disease [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is considered a key element in the development of atherosclerosis cardiovascular disease and has been associated with systemic inflammatory disorders such as diabetes, obesity, or metabolic syndrome. Hyperoxaluria has also been reported to cause systemic ED both in animal models and cell culture studies [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ED has been linked to urolithiasis through clinical and experimental studies [6][7][8][9]. The aim of this review is to summarize the current knowledge and the latest findings on the pathogenic mechanisms underlying endothelial dysfunction in urolithiasis, paying special attention to the role of the reactive oxygen species (ROS) as an underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%